Severe nummular eczema in childhood. Experience of six cases managed with oral methotrexate. - Sepúlveda, A.; Truffello, D.; Fuenzalida, H.; Macías, M.A. (European Journal of Pediatric Dermatology, 2019)
Nummular eczema in children is a chronic disease characterized by coin shaped pruritic patches that can affect any part of the body and according to its severity can greatly compromise the quality of life. The first line of treatment of this skin disorder is based on general care associated with use of local corticosteroids, often without obtaining satisfactory improvement, especially in severe cases. The objective of this study is to describe the experience of the use of oral methotrexate in a series of cases of children with severe nummular eczema with 6 months of follow-up. A retrospective descriptive study using clinical records of pediatric patients with severe nummular dermatitis managed with oral methotrexate between January 2017 and December 2018 was performed. Medical records of six patients were collected, 5 male and 1 female, mean age 7.8 (range 5 to 10 years). The average duration of treatment was 12 months. The patients presented good response and tolerance to the medication, achieving clearance of the lesions by ≥ 90% (4 patients equal to 66,7%), and 50-89% (2 patients equal to 33,3%) in an average of 2,8 months. Oral methotrexate could be an effective, safe and well tolerated alternative in pediatric patients with recalcitrant nummular eczema.